PENDEKATAN SOCIAL DILEMMA PADA KAJIAN EKONOMI, MANAJEMEN, DAN BISNIS - Siswanto, Bambang (Manajemen Bisnis Kompetensi, 2017)
ABSTRACTMost of the research is done to get interaction solutions that are social dilemma. At first the social dilemma was a study of the field of psychology, but now has been growing in other fields such as economics, management, business, accounting, social, computer and decision-making techniques, even ecological and evolutionary biology. The focus of the study on economics, management, and business is how to increase the desire of economic agents, management decision makers, and business people to choose cooperative strategies. The results of the literature review show openness and communication is a solution that empirically managed to improve cooperation.Ã‚Â Keywords: social dilemma, cooperation, communication